(untitled) (The International Journal for Scientific Research, 2025)
This study was conducted in Misurata city, which mainly depends on the Great Man-Made River water to provide it with drinking water. The city faces problems in water supply due to the shortage and fluctuation in water supplies coming from outside the city through the Great Man-Made River system, especially in the summer. The lack of sufficient quantities of water to meet the needs of the population forced officials and most of the population to dig many groundwater wells to fill the resulting water deficit. This study aims to use the Groundwater Quality Index (GWQI) to determine the suitability of groundwater quality for drinking in selected wells in Misurata city as well as its suitability for irrigation by calculating a set of properties such as electrical conductivity, residual sodium carbonate (RSC), chloride and sodium adsorption ratio (SAR). Five samples were taken: two samples from Sidi Mubarak area (a sample from well 1B and a sample from the man-made river that supplies this area (Sidi Mubarak area) with drinking water B2), a sample was also taken from the burial area B3, a sample was also taken from the main Sikt reservoir B4 (Sikt area) that supplies the city with the man-made river water, and a sample of bottled drinking water B5 was taken from the local market for comparison. From the results, we note that samples B1 and B3 are not suitable for drinking, while samples B2, B4, B5 are considered good for drinking according to (GWQI). Regarding their suitability for irrigation water, salinity ranged between very high B1, B3 and high B2, B4. The RSC values ​​obtained for all samples were negative for all study wells, which means that all well samples are considered suitable for irrigation. The SAR for all well samples was classified as low sodium, which indicates that well water can be used for irrigation purposes in different types of soil and does not affect soil permeability and filtration rate.